Muslim Women’s Narratives of Veiling and Identity in Post-Soviet Contexts - Lange, Alena (Journal of religion in Europe, 2022)
Based on ethnographic materials, the article discusses Muslim women’s narratives as an expression of the process of identity negotiation in the post-Soviet cultural context. Muslim women’s narratives based on Islamic, ethnic, gendered epistemologies are intertwined with each other and hybrid. Muslim-Tatar women’s identity as women, Muslims and Tatars is tied together, while simultaneously being fragmented and peripheral to male identity. Since the Russian state imbues veiling with political meaning, Muslim women identity is politicized, therefore veiling as a part of Muslim-Tatar women’s identity is negotiated not only inside of the Muslim-Tatar community, but outside due to external discourses.